Meta-Analysis of Real-World Clinical Practice to Assess the Effectiveness of Riociguat in Treating Chronic Thromboembolic Pulmonary Hypertension - Pamukcu, Esra; Kaya, Mehmet Onur (Wiley, 2025)
Riociguat is a drug that improves hemodynamic parameters and increases the exercise capacity of patients with chronic thromboembolic pulmonary hypertension (CTEPH). This meta-analysis evaluated cohort studies that measured changes in parameters such as the 6-minute walk distance (6MWD), mean pulmonary arterial pressure (mPAP), pulmonary vascular resistance (PVR), cardiac output (CO), and pulmonary arterial wedge pressure (PAWP). The study utilized cohort studies with a paired samples group design to measure the changes in these parameters. We searched for articles containing the keywords Riociguat and Chronic thromboembolic pulmonary hypertension in their titles in PubMed, Web of Science, Scopus, and ScienceDirect databases until May 2024. We conducted five meta-analyses to combine the mean difference values. We identified nine studies that examine the effects of Riociguat on patients. Analyzing data from 565 patients revealed that Riociguat increases the distance walked during the 6MWD test by an average of 35.86 m. After analyzing data from 717 patients, it was found that Riociguat reduces mPAP by an average of 9.23 mm Hg. Analyzing data from 586 patients, it was found that Riociguat reduces PVR by an average of 220.11 dyn.s.cm-5${\mathrm{dyn}}.{\mathrm{s}}.{\mathrm{c}}{{{\mathrm{m}}}<^>{ - 5}}$. Moreover, analyzing data from 643 patients showed that Riociguat increases CO by an average of 0.49 L/min. Finally, after analyzing data from 645 patients, it was concluded that Riociguat treatment did not have a statistically significant effect on PAWP. Our findings indicate that Riociguat improved certain hemodynamic parameters and exercise capacity in CTEPH patients.
Keywords: Chronic thromboembolic pulmonary hypertension; Meta-analysis; Riociguat; Systematic review